Role of benzyladenine and gibberellic acid in alleviating water-stress effect in gram (Cicer arietinum) - YADAV, NEELAM; GUPTA, V; YADAV, V K (The Indian Journal of Agricultural Sciences, 2013)
Two gram (Cicer aerietmum L.) genotypes,’C 235’ (susceptible) and ’RSG 143-1’ (moderately tolerant to water stress), were grownÂ in earthen pots. One set of plants were subjected to water stress only once (S1) at days after sowing and another set twice (S2) at 45 and 80 days after sowing. Both the control (non-stress) and stressed plants were sprayed with benzyladenine and gibberellic acid separately at the time of imposing stress. Water stress increased the proline, amino acids and total and total soluble sugars but decreased the soluble proteins and starch content in the leaves. Spray of hormones stimulated accumulation of all these metabolites, especially under water stress in both the genotypes. Stress-induced increase in amino acids, particulary of proline and soluble sugars, might be responsible for osmotic adjustment. Spray of benzyladenine and gibberellic acid could alleviate adverse effect of water stress partly in both the genotypes especially in ’RSG 143-1’,Gibberellic acid was more effective in ameliorating water-stress effect than benzyladenine in both the genotypes.